Congenital Neurofibromatosis in a Saudi Neonate who Presented with Neck Mass, Esophageal and Airway Obstruction - Mersal, Ali Y. (Medknow Publications & Media Pvt Ltd, 2012)
We are presenting a case of a neonate presented with a neck mass, airway and esophageal obstruction, the tumor has a brain extension; treated with partial surgical excision; the pathological studies revealed plexiform Neurofibromatosis. The patient also has café au lait spots.